2017
DOI: 10.1055/s-0037-1604471
|View full text |Cite
|
Sign up to set email alerts
|

Preeclampsia

Abstract: The authors review hypertensive disease during pregnancy with an academic and practical view, and using the best evidence available. This disease, which is the most important clinical disease in Brazilian pregnant women, may have its incidence reduced with prevention through the use of calcium and aspirin in pregnant women at risk. Previously, it was a disease that presented with hypertension with proteinuria, but it has now been classified with new clinical parameters besides proteinuria. Morbidity and mortal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
86
1
21

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(110 citation statements)
references
References 77 publications
2
86
1
21
Order By: Relevance
“…A previous study reported that E2 suppressed the binding activity of NF-κB mediated by ERα66 and reduced the expression of MMP2, MMP9, cyclin A and cyclin d1, resulting in cell cycle arrest and promoting cell apoptosis (36). Apoptotic processes and endothelial dysfunction are common in PE (3). The results of the present study indicated that that E2 suppressed the expression of MMP9, MMP2 and VcAM-1 in placental tissue induced by L-NAME treatment.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…A previous study reported that E2 suppressed the binding activity of NF-κB mediated by ERα66 and reduced the expression of MMP2, MMP9, cyclin A and cyclin d1, resulting in cell cycle arrest and promoting cell apoptosis (36). Apoptotic processes and endothelial dysfunction are common in PE (3). The results of the present study indicated that that E2 suppressed the expression of MMP9, MMP2 and VcAM-1 in placental tissue induced by L-NAME treatment.…”
Section: Discussionsupporting
confidence: 54%
“…It is the major cause of maternal and perinatal death, premature birth and fetal growth restriction; the pathogenesis is complex and effective treatments are currently lacking (1,2). PE is a chronic disease, which frequently leads to multiple organ failure in the body of the pregnant woman, increases the production of reactive oxygen species, causes maternal inflammation and accelerates apoptosis, leading to an imbalance between the formation of normal placentation and pro-angiogenic factors (3). Previous studies have demonstrated that compared with non-pregnant females, those with normal pregnancy and patients with PE exhibit an inflammatory response, and that patients with PE exhibit excessive activation of the inflammatory response compared with normal pregnant subjects, including increased levels of inflammatory cytokines and products of oxidative stress (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…It can be accompanied by abnormal changes in the heart, lung, liver, kidney, and other vital organs or the blood system, digestive system, nervous system, and placenta-fetal interface, and thus is a major cause of morbidity and mortality in maternal and fetal medicine [2,3]. The incidence of PE is estimated to be 3-5% of pregnancies worldwide [4], but 8.1% in developing countries, which the mortality rate for mothers can reach 22.0% [5]. The clinical symptoms of PE are reflected in three aspects; the first involves placental perfusion dysfunction followed by a systemic inflammatory response, the second is vascular endothelial damage, and the last is oxidative stress [1].…”
Section: Introductionmentioning
confidence: 99%
“…Preeclampsia is defined as a multisystemic disease characterized by a combination of elevated blood pressure (systolic BP ≥140 mmHg or diastolic BP ≥ 90 mmHg), first identified after 20 weeks of gestation, and proteinuria, and may coincide with another hypertensive state (4) .…”
Section: Introductionmentioning
confidence: 99%